2011
DOI: 10.1063/1.3610549
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the conformation of DNA dodecamer segment: A simulation study

Abstract: Different solvent temperatures with five kinds of counterions are used to investigate solvent effects on the DNA microscopic structure. The dodecamer d (CGCGAATTCGCG) DNA segment is merged into the solvents and its conformation transition is studied with the molecular dynamics simulations in detail. For the simple point charge model of water molecule with Na(+) counterions, as temperature increases from 200 K to 343 K, the duplex DNA changes from stiff B form to a state between A form and B form, which we defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 76 publications
(84 reference statements)
2
26
0
Order By: Relevance
“…72,82 Furthermore, the size of dehydrated Cs + is too large to fit the cavity of the G-quartet. 87 Further addition of salts leads to a decrease in R h , which is the result of the formation of the G-quadruplex and the decrease in the intramolecular electrostatic repulsion as discussed before, and the concentration required to induce a decrease in R h of each cation obeys the order K + (B10.0 mM) o Na + (B100.0 mM) o Cs + E Li + (B1.0 mM). 7(a).…”
Section: View Article Onlinementioning
confidence: 76%
“…72,82 Furthermore, the size of dehydrated Cs + is too large to fit the cavity of the G-quartet. 87 Further addition of salts leads to a decrease in R h , which is the result of the formation of the G-quadruplex and the decrease in the intramolecular electrostatic repulsion as discussed before, and the concentration required to induce a decrease in R h of each cation obeys the order K + (B10.0 mM) o Na + (B100.0 mM) o Cs + E Li + (B1.0 mM). 7(a).…”
Section: View Article Onlinementioning
confidence: 76%
“…[69][70][71] The counter ion layer is too stable to be removed by conventional deionization methods. However recent research found that an electric field can promote the dissociation of the DNA-ion complex during capillary electrophoresis resulting in irregular DNA migration velocity.…”
Section: Dnmp Phosphate Association With Sodium Ionsmentioning
confidence: 99%
“…After that, the following simulations of 60 ns are carried out for dynamics and structure analyses. The structure parameters are analyzed by the program Curves [46][47][48][49] continually for the precise values (the width and depth of the minor groove are defined in detail in Ref. [46]).…”
Section: Theory and Simulation Detailsmentioning
confidence: 99%